RECONSTRUCTION OF LIABILITY NOTARY PUBLIC OFFICERS TO ACT AS A VALUE-BASED JUSTICE - Elpina Elpina; Eman Suparman; Jelly Leviza (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Notary is a public official who is authorized to make authentic certificates and other authorities referred to in Article 1 (1) of Law No. 30 of 2004. Through the deed he had done, the notary must be able to provide legal certainty to users notary services. Deed made by or before a notary may be authentic proof in providing legal protection to the other parties concerned to the deed regarding the certainty of events or legal actions that do Notary is a professional in his duties should be based on the setting in legislation or code ethics into its internal settings. This research is empirical juridical and socio legal research with constructivism. To answer the question in this study the sociological approach of law. Supervision of the notary in order to uphold the dignity Notary office. Notary responsibility as a public official related to material truth, which is liable to civil Notary of the material truth of the deed he had made; Notary criminally liable for the truth material in deed he made; responsibility Notary Regulation Notary of the material truth in deed that made ;, and responsibility in performing tasks Notary office by a Notary ethical code. Reconstruction accountability Notary as a public official in the deed based on the values of justice through law enforcement against Notary mewujudukan legal certainty based on values of Pancasila, rekonsturksi legal relationship Notary with the parties, the reconstruction of the rights and obligations dissenter Notary, as well as the reconstruction of Article 65 of Law Notary to Notary time limit liability. Suggested to the Notary in their duties must have the precision, which this austerity is acting honestly, thoroughly, independently, impartially, and safeguard the interests of the parties involved in a legal action. Keyword: Accountability, Notary Public, PPAT, Creating Authentic Deed, The Value of Justice.